ANALISIS KANDUNGAN BORAKS (Na2B4O7 10 H2O) PADA ROTI TAWAR YANG BERMEREK DAN TIDAK BERMEREK YANG DIJUAL DI KELURAHAN PADANG BULAN KOTA MEDAN TAHUN 2012 - Imee Syorayah Pane; Devi Nuraini Santi; Indra Chahaya (Lingkungan dan Kesehatan Kerja, 2013)
Analysis of Borax (Na2B4O7 10 H2O) in Branded and Unbranded White Bread Which is Sold in Padang Bulan Subdistrict Medan 2012. White bread is one of perishable foods. Wheat flour as white bread ingredients containing high starch and it is a source of nutrients for microorganisms. Therefore, it is required the addition of presentatives into the white bread dough to extend the usage period. Harmful food additives should not be present in food. One of them is borax. The purpose of this research was was to determine whether there is borax in branded and unbranded white bread that is sold in Padang Bulan Subdistrict, Medan.The research was a descriptive survey to determine the presence of borax in branded and unbranded white bread.The results showed that laboratory test result with flame test methods and the reaction of curcumin, there was no branded and unbranded white bread containing borax.Presentative which used in some white bread is calcium propionate and acetic acid. Food additives such as emulsifiers, acidity regulator and bread improver including packaging and storage procedure can affect the quality and usage period of white bread.It can be concluded that white bread is safe to consume because it does not contain borax for the purpose of preservation. However, there should be supervision, counseling by the relevant agencies (Departement of Health) on food Additives which are safe for consumption to producers and consumers. Consumers are expected to be wise in choosing food products. To producers are expected to include the label expiration date, license from Health Departement/ BPOM, as well as a complete composition on white bread packaging as information to consumers who will buy white bread. Keywords: Borax, Branded White Bread, Undbranded White Bread.